Modulation of chymase-mediated rat serosal mast cell degranulation by trypsin or diisopropyl fluorophosphate. - Schick, B (1989)
Exposure of rat serosal mast cells (RSMC) to chymase, an endogenous secretory granule serine protease, at 37 degrees results in exocytosis, as determined by beta-hexosaminidase release. As the number of RSMC is increased with a set amount of chymase, the net percentage beta-hexosaminidase release decreases linearly, implying a finite set of cellular interactions per chymase unit. Pretreatment of RSMC with trypsin at 37 degrees renders them refractory to subsequent exocytosis mediated by chymase in a dose- and time-dependent fashion, with complete refractiveness occurring by 15 min at 37 degrees with 2.5 micrograms trypsin/ml. Anti-IgE-mediated coupled activation-secretion of RSMC is not affected by the same trypsin pretreatment. When RSMC are pretreated with trypsin (2.5 micrograms/ml) for 0-120 min at 1 degree a progressive loss of sensitivity to activation by chymase at 37 degrees occurs. RSMC susceptibility to chymase-mediated degranulation after trypsin pretreatment can be partially regenerated by culturing the RSMC for about 24 hr in medium at 37 degrees. These findings suggest that a trypsin-sensitive constituent, possibly a receptor or substrate, is necessary for the functional interaction of chymase with RSMC. When added with diisopropyl fluorophosphate (DFP), chymase does not induce RSMC degranulation at 37 degrees. However, if the DFP is removed before addition of chymase at 37 degrees or is added after the chymase-priming event occurs at 1 degree, subsequent degranulation at 37 degrees is not inhibited. Thus, the induction and not the secretion phase is DFP-inhibitable in chymase-induced activation-secretion. In addition, the priming but not the exocytosis phase of chymase-initiated RSMC activation-secretion, which is not dependent on temperature and calcium ion concentration, involves a cellular trypsin-sensitive protein.